2020
DOI: 10.3389/fmicb.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

Phage Lytic Protein LysRODI Prevents Staphylococcal Mastitis in Mice

Abstract: Phage lytic proteins are promising antimicrobials that could complement conventional antibiotics and help to combat multi-drug resistant bacteria that cause important human and animal infections. Here, we report the characterization of endolysin LysRODI (encoded by staphylophage phiIPLA-RODI) and its application as a prophylactic mastitis treatment. The main properties of LysRODI were compared with those of endolysin LysA72 (encoded by staphylophage phiIPLA35) and the chimeric protein CHAPSH3b (derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…To date, several works have demonstrated the high in vitro and in vivo activity of endolysins against S. aureus isolates from different origins, including clinical staphylococci (revised by Gutiérrez et al [45]). The lytic protein used in this study, LysRODI, had been previously shown to be highly active against different staphylococcal strains [24]. Along the same lines, the data presented here indicates that all clinical MRSA isolates were susceptible to LysRODI, although to different degrees.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…To date, several works have demonstrated the high in vitro and in vivo activity of endolysins against S. aureus isolates from different origins, including clinical staphylococci (revised by Gutiérrez et al [45]). The lytic protein used in this study, LysRODI, had been previously shown to be highly active against different staphylococcal strains [24]. Along the same lines, the data presented here indicates that all clinical MRSA isolates were susceptible to LysRODI, although to different degrees.…”
Section: Discussionsupporting
confidence: 77%
“…Our laboratory has already demonstrated the potential of several phage endolysins to remove S. aureus cells from different environments. For example, various endolysins and chimeric proteins showed lytic activity against S. aureus cells in pasteurized milk [25,26] and biofilms [24,27,28]. Moreover, we showed that subinhibitory doses of some endolysins can inhibit biofilm formation in S. aureus through the downregulation of autolysin-encoding genes [28].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations